HIGH ECONOMIC GROWTH: WILL ENSURING INCLUSIVE GROWTH? - Soleh, Ahmad; Sukiyono, Ketut; Nurazi, Ridwan (Journal of Research in Business, Economics, and Education, 2020)
Inclusive growth (IG) measures the benefits of economic growth for people's welfare. Several approaches have been developed in measuring inclusive growth. This study aims to measure inclusive growth using the poverty approach (IGp). This research was conducted in Jambi province and Kepulauan Riau province which is the region with the highest average economic growth on the island of Sumatera in the period 2001-2016. The method of approach used in this study is descriptive analysis. The technique of collecting data uses library research. The poverty-equivalent Growth Rate (PEGR) was developed in the measurement of inclusive growth. The results of the study show that high economic growth does not guarantee the achievement of inclusive growth. This phenomenon is indicated by the average incremental growth coefficient (IGp) of Jambi province of 0.038 lower than the average coefficient of economic growth (?g) of 0.060. The same condition occurs in the province of Riau Islands, the average inclusive growth coefficient (IGp) is 0.020 lower than the average coefficient of economic growth (?g) of 0.062. This indicates that high economic growth has not been distributed evenly and the benefits of face economic growth are accepted by non-poor people. Some government policies and programs are expected to be directed towards efforts to reduce poverty so that the benefits of economic growth are truly accepted by the poor.